Successful Surgical Treatment of Q Fever Endocarditis with Mitral Valve Repair. Issue 2 (1st June 2012) - Khan, JN; Tapp, LD; Glancy, JM; Prasad, N; Bailey, MS; Graham, Timothy R
Abstract : We report a case of successful surgical treatment of Q fever endocarditis with mitral valve repair in a 66-year old retired British soldier. Valve replacement is invariably undertaken in Q fever endocarditis due to the degree of valvular damage and concerns about eradicating the organism, Coxiella burnetii . Our unique case allowed valve repair since pre-existing myxomatous degeneration and subsequent posterior mitral valve leaflet prolapse resulted in significant excess valve tissue, allowing quadrangular resection of the damaged and perforated P2 portion of this leaflet. Follow-up at four years (including three years of antibiotic treatment) has confirmed excellent valve repair, with no echocardiographic, clinical or microbiological evidence of recurrence. We are only the second group to describe valve repair in a patient with chronic Q fever endocarditis. Valve repair is preferable to valve replacement for Q fever endocarditis, if technically possible .